Generalized Nagumo Model: Interesting Effects of Parameters's Fluctuations - Mangioni, Sergio Enrique (2015)
In this paper, we used an analytical method to calculate the effects that produce the parameter’s fluctuations characterizing a generalization of Nagumo model. (The extinction option is replaced by one of low density homogeneous population.) Moreover, we also check the results by means of numerical simulations of the corresponding stochastic process. We find that these fluctuations have a strong impact on the solutions producing interesting changes.